Classifying individual differences in interoception: Implications for the measurement of interoceptive awareness - Murphy, J; Catmur, C; Bird, G (Springer, 2019)
It has been suggested that individual differences in interoception (the perception of the body’s internal state) can be divided into three distinct dimensions: interoceptive accuracy (performance on objective tests of interoceptive accuracy), interoceptive sensibility (self-reported beliefs concerning one’s own interoception) and interoceptive awareness (a metacognitive measure indexed by the correspondence between interoceptive accuracy and interoceptive sensibility). Research conducted under this model underscores the importance of interoceptive awareness for a variety of disorder-specific and transdiagnostic symptoms. However, the clinical importance of interoceptive awareness means that this aspect of interoception warrants further scrutiny, and such scrutiny suggests that revision of the three-dimensional model of interoception is necessary. In this theoretical paper, we outline such a revision, highlighting a need to distinguish not only how interoception is measured (objective measures vs. self-report), but also what is measured (accuracy vs. attention). The model refines how individual differences in interoception are categorised, with important consequences for the measurement of interoceptive awareness. Such a revision may help researchers to identify the strengths and weaknesses in interoception observed across clinical conditions, and to isolate clinically relevant individual differences.